“Koh Ngomong” and a Desire to Do Whistleblowing: An Experimental Study - Ayu Aryista Dewi; Dodik Ariyanto (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
The issue of whistleblowing has attracted attention several decades ago until now. The interesting trigger for whistleblowing issues is the increase in the frequency or number of violations of organizations around the world and massive media coverage. The aim of the study is to analyze the influence of the Koh Ngomong attitude towards the intention to do whistleblowing. The study also examined the effect of the Koh Ngomong attitude on the tendency of employees to choose internal or external reporting channels. Subjects in this study were students in Magister of Accounting, Faculty of Economics and Business, Udayana University, Bali. The subject acts as a surrogate of a management accountant who reports a fraud (whistleblower). This study uses the between subject experimental method, with 2x2 factorial design manipulation. Analysis tool using Analysis of Variance (ANOVA). The results of the study show that there is no difference in the reporting path between Koh Ngomong and non Koh Ngomong groups to become a whistleblower.